Assessing Independence in Instrumental Activities of Daily Living (IADL) Among Elderly Patients with Knee Osteoarthritis: A Study at the Geriatric Clinic - Angga Sri Hidayana; Arief Yanto; Tri Hartiti; Vivi Yosafianti Pohan (Media Keperawatan Indonesia)
Knee osteoarthritis is a common degenerative condition among the elderly, leading to a significant decline in functional ability and increased dependency in daily activities. This study aimed to analyze the level of independence and pain distribution among elderly patients with knee osteoarthritis at the Geriatric Polyclinic of a General Hospital. A descriptive design was utilized, using secondary data from 150 elderly patients diagnosed with knee osteoarthritis. Independence levels were assessed using the Instrumental Activities of Daily Living (IADL) scale, while pain location data were retrieved from medical records. The findings revealed that 72.7% of patients maintained independence, while 27.3% required assistance, with bilateral pain reported in 87.3% of cases. Most patients were aged 71–90 years, with a predominance of females (78.7%). These results indicate that the majority of elderly patients with knee osteoarthritis remain functionally independent, although age and gender significantly influence the prevalence and severity of the condition.